Razvoj učnih spretnosti pri pouku likovne umetnosti - Arov, Helen (Revija za elementarno izobraževanje, 2017)
This study focused on middle school art teachers supporting the development of students% learning skills, specifically their awareness of the framework of learning skills. It also looked at the relations between the teaching practices teachers use for supporting learning skills and students' learning motivation in art classes. The study combined qualitative and quantitative research methods. The class observations and interviews were conducted with ten Estonian middle school art teachers. One hundred and forty-eight students from the observed classes filled out the learning motivation questionnaire about their interest and achievement goals in visual arts. The study draws attention to the importance of teachers being aware of and valuing learning skills alongside subject specific knowledge, as it could enhance students' autonomous motivation and support adaptive goal setting.
Keywords: learning skills; učne spretnosti; učna motivacija; learning motivation; načini poučevanja; teaching practices; middle school; srednje šole; art education; likovna vzgoja